PERANAN ADPEL DALAM MENUNJANG KELANCARAN ANGKUTAN LAUT - Nuraini Nuraini (Universitas Batanghari Jambi, 2014)
Based On Government Regulation And Letter Of Decision Ministerial, The Jambi Administration Port Office To Be On Duty For Execute Loading And Unloading The Ship, And Then Applied In Accordance With Standard Operational Procedure. The Execution Applied With Intern Coordination And Extern Coordination.All Kinds Of Cooperation With Another Instance Trough Communication And Information, Meeting And Other Form Of Cooperation Are Expected To Support The Activities.Factors Supporting The Loading And Unloading Of The Ship Is The Existence Of Good Cooperation Of All Official And Officers In A Variety Of Activities And There Is Good Cooperation Between Related InstitutionsWhereas The Inhibiting Factors Is Unclear And Incomplete Administrative Requirements, Unfavorable Weather, The Batanghari River Increasingly Shallow And Then Causing The Ship Can Not DockKey Words : Service, Interrelation, Port Office